2020
DOI: 10.24138/jcomss.v16i2.974
|View full text |Cite
|
Sign up to set email alerts
|

A Level-Wise Periodic Tree Construction Mechanism for Sleep Scheduling in WSN

Abstract: The wireless sensor network (WSN) has been extensively used to monitor and control the natural ecosystem on a large scale like air quality, natural life, etc. Low battery power,low storage, and limited processing ability are the most critical areas of concern in WSN. To reduce energy utilization, the sensor nodes in WSN work in a cyclic process between active and sleep mode. A certain number of nodes are chosen active and they are responsible for sensing as well as data transmission and rest of the nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To fulfill the primary objective of WSN, i.e., sense the whole deployed area along with maintaining network lifetime, the proposed level-wise tree construction approach includes the area coverage into consideration to fulfill the above two requirements. To validate the efficiency of the proposed algorithm with respect to network lifetime, in figure 4.1, we compare the number of nodes alive after each tree reconstruction round in the proposed approach compared to the normal level-wise approach given [27]. From this figure, it is observed that after 46 th round, the nodes start dying out in both the earlier approach and the proposed approach.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To fulfill the primary objective of WSN, i.e., sense the whole deployed area along with maintaining network lifetime, the proposed level-wise tree construction approach includes the area coverage into consideration to fulfill the above two requirements. To validate the efficiency of the proposed algorithm with respect to network lifetime, in figure 4.1, we compare the number of nodes alive after each tree reconstruction round in the proposed approach compared to the normal level-wise approach given [27]. From this figure, it is observed that after 46 th round, the nodes start dying out in both the earlier approach and the proposed approach.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In order to evaluate the longevity of the proposed protocol, we simulated both the earlier approach [27] as well as the proposed approach to identify the number of sleep nodes present in different rounds of the tree reconstruction as shown in figure 4.6. This figure ensures that the network lifetime achieved through the proposed approach is far better than the earlier level-wise tree construction approach.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation